Finite elements in convection dominated flows: a semi-Lagrangian method. - Silva, Hugo Marcial Checo (2011)
Convection dominated flows represent a challenge for finite element method simulation. Many methods have been developed to address this problem. In this work we compare the performance of two methods in the solution of the convectiondiffusion and Navier-Stokes equations on environmental flow problems: the Streamline Upwind Petrov Galerkin (SUPG) and the semi-Lagrangian method. In Galerkin finite element methods for fluid flows, the matrix associated with the convective term is non-symmetric, and as a result, the best approximation property is lost. In practice, solutions are often corrupted by espurious oscillations. In this work, we present a semi- Lagrangian method, which is implicitly an upwind method, therefore solving the spurious oscillations problem, and a comparison between this semi-Lagrangian method and the Streamline Upwind Petrov Galerkin (SUPG), an stabilizing method of recognized performance. The SUPG method takes the interpolation and the weighting functions in different spaces, creating an effect so that the spurious oscillations are drastically attenuated. The semi-Lagrangean method is a integration factor method, in which the factor is an operator that shifts to a coordinate system that moves with the fluid, but it resets the Lagrangian coordinate system after each time step. This provides stability and the possibility to take bigger time steps. There are many works in the literature analyzing stabilized methods, but they do not analyze the semi-Lagrangian method, which represents the main contribution of this work: to recognize the strengths and weaknesses of the semi-Lagrangian method in convection dominated flows.